The impact of transaction tax on price volatility and trading volume / Mohd Hussin Abdul Lasim - Abdul Lasim, Mohd Hussin (2016)
This research paper investigates the relationship between Securities Transaction Tax(STT) and trading volume and price volatility. This study gives us an opportunity to test the effect of the transaction tax rate on trading volume and price volatility of certain countries that imposed STT. Previous studies have found that there is a relationship between transaction tax and trading volume and the price volatility that significantly relate to the changes of the transaction tax. We found that the trading volume decreased in the period after the increment of the transaction tax. Other than that, the argument that the increasing of STT may have influenced price volatility was supported by our findings. The result reveals that security transaction tax affects the price volatility and the trading volume significant to the changes of STT.